Improve Learning Programming through Small Private Online Course and Virtual IDE - Muhammad Taufiq Zulfikar (Bina Nusantara University, 2023)
In learning programming languages ​​there are some technical problems such as the difficulty of installing IDE applications and tend to be heavy, cannot be used on various operating system platforms and there are no programming tutorials. By providing online and open learning content for certain organizations or often called SPOC (Small Private Online Course) and Virtual IDE to support SPOC, it can help students to improve programming skills. The purpose of this research is to create a SPOC LMS that has a Virtual IDE as a learning support. The Quantitative Method was used as a research method in this study to make a conclusion from the experimental results. The results of this study concluded that LMS SPOC and Virtual IDE can help students understand language programming.